The assessment of work productivity and activity impairment in Behcet's disease - ALİBAZ ÖNER, FATMA; MUMCU, GONCA; İNANÇ, GÜZİDE NEVSUN; DİRESKENELİ, RAFİ HANER; ERGUN, SAFİYE ATLAS TÜLİN (TUBITAK SCIENTIFIC & TECHNICAL RESEARCH COUNCIL TURKEY, 2017)
Background/aim: The aim of this study was to assess the relationships between the course of Behcet's disease (BD), disease-specific fears, and work productivity and activity impairment. Materials and methods: In this cross-sectional study, 110 consecutive BD patients were included. The Work Productivity and Activity Impairment questionnaire was used. Results: In the group of employed patients, 30.41% had missed work during the previous week. The mean percentages of daily activity impairment were higher in patients with musculoskeletal involvement (39.81 +/- 33.61%) compared to those without (23.48 +/- 32.45%) (P = 0.008). A greater decrease in working hours was observed in patients with eye involvement (45.52 +/- 15.29 h) compared to those without (54.15 +/- 15.29 h) (P = 0.007). More of the male patients (67.8%) were afraid of losing their jobs compared to females (30%) (P = 0.000). Conclusion: The highest levels of lost productivity and the most severe effects on daily life are consequences of eye and musculoskeletal involvement in the study population. More effective therapeutic approaches are required to improve the working lives of patients with BD. Moreover, male patients had a higher fear of losing their jobs, suggesting a match between the expected clinical course and the predictions of BD patients.
Keywords: Behcet's disease; work productivity; activity impairment; QUALITY-OF-LIFE; RHEUMATOID-ARTHRITIS; INDIRECT COSTS; DISABILITY; HEALTH; IMPACT; PARTICIPATION; BURDEN; RISK